2011
DOI: 10.1186/1471-2377-11-42
|View full text |Cite
|
Sign up to set email alerts
|

Perceived wellbeing of patients one year post stroke in general practice - recommendations for quality aftercare

Abstract: BackgroundAnnually, 41,000 people in the Netherlands have strokes. This has multiple physical and psychosocial consequences. Most patients return home after discharge from hospital. Quality aftercare by general practitioners is important to support patients at home. The purpose of this study is to examine the wellbeing of patients who returned home immediately after discharge from hospital, one year post stroke, in comparison with the general Dutch population of the same age and to determine factors that could… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
36
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 38 publications
6
36
0
2
Order By: Relevance
“…), patients, and their families. Our findings may be useful for policy makers to understand the family and medical-social contexts of stroke over time in order to design adequate health systems [51,52]. …”
Section: Discussionmentioning
confidence: 99%
“…), patients, and their families. Our findings may be useful for policy makers to understand the family and medical-social contexts of stroke over time in order to design adequate health systems [51,52]. …”
Section: Discussionmentioning
confidence: 99%
“…However, recently, it has been reported that nearly half of stroke survivors experienced significant negative psychological outcomes associated with stroke such as depression and that social support mediated both QoL and functional ability (Huang et al, 2010). In a Danish and Netherlands cohort, stroke survivors who experienced depression were less likely to regain their baseline QoL when compared with those who did not experience depression (De Weerd, Rutgers, Groenier, & van der Meer, 2011; Muus, Petzold, & Ringsbert, 2010). …”
Section: Stroke Qol and Lonelinessmentioning
confidence: 97%
“…Broadening our nursing knowledge to include studies of the negative psychological outcomes of stroke, such as anxiety(De Weerd et al, 2011), depression (De Weerd et al, 2011; Huang et al, 2010), and loneliness (Hilari et al, 2010), and enhancing our understanding of how they relate to QoL could lead to new nursing interventions that target the emotional health needs of the stroke survivor. Few studies have focused on loneliness as a specific negative psychological outcome of stroke.…”
Section: Stroke Qol and Lonelinessmentioning
confidence: 99%
“…A stroke has considerable impact on the patient’s life and his/her family [2,3]. Stroke can cause various neurological deficits, including paralysis, loss of vision, aphasia, spatial disorder, disturbance in thinking, difficulty in swallowing and incontinence [4].…”
Section: Introductionmentioning
confidence: 99%